Antiproliferative Sorbicillinoids From the Deep-Sea-Derived Penicillium allii-sativi - Xie, Chun-Lan; Zhang, Duo; Lin, Ting; He, Zhi-Hui; Yan, Qing-Xiang; Cai, Qi; Zhang, Xiao-Kun; Yang, Xian-Wen; Chen, Hai-Feng (Frontiers in Microbiology, 2021)
Two new (1–2) and three known (3–5) sorbicillinoids were isolated from the deep-sea-derived fungus Penicillium allii-sativi MCCC 3A00580. Compounds 1 and 2, named sorbicatechols C and D, were two new hybrid dihydrosorbillinoids. Their structures were established mainly by spectroscopic analyses and ECD calculations. All five isolates were tested for antiproliferative activities against four tumor cell lines of MCF-7, HT-29, HuH-7, and LNCap. Compounds 2 and 5 inhibited HT-29 cells in a good dose-dependent manner. Mechanism investigation uncovered that they could significantly induce cell cycle G2-M phase arresting by increasing the protein levels of p-H3 and cyclin B1.